P2X7 receptor in the trigeminal sensory nuclear complex contributes to tactile allodynia/hyperalgesia following trigeminal nerve injury. (3rd August 2012) - Ito, G.; Suekawa, Y.; Watanabe, M.; Takahashi, K.; Inubushi, T.; Murasaki, K.; Hirose, N.; Hiyama, S.; Uchida, T.; Tanne, K.
Abstract Background The present study directly addresses the roles of the P2X7 receptor (P2X7R), an ionotropic adenosine triphosphate (ATP) receptor, and cytokines in the induction of orofacial pain following chronic constriction injury (CCI) of the infraorbital nerve (IoN). Methods Rats were anesthetized, and ligatures of 4‐0 chromic gut were tied around the IoN. A438079, a P2X7R antagonist or SB203580, a phosphorylated (p)‐p38 mitogen‐activated protein kinase (MAPK) inhibitor, was infused intrathecally into CCI‐treated rats. In another group of rats, 3′‐O‐(4‐benzoylbenzoyl) adenosine 5′‐triphosphate (BzATP), a P2X7R agonist, was infused intrathecally with A438079, SB203580 or etanercept, a tumor necrosis factor (TNF)‐α receptor‐binding recombinant drug. Results CCI of the IoN induced tactile allodynia/hyperalgesia and up‐regulation of P2X7R, membrane‐bound TNF‐α (mTNF‐α) and soluble TNF‐α (sTNF‐α) in the trigeminal sensory nuclear complex (TNC). Tactile allodynia/hyperalgesia or up‐regulation of mTNF‐α and sTNF‐α in the TNC following CCI of the IoN was inhibited by A438079. SB203580 also attenuated tactile allodynia/hyperalgesia or up‐regulation of mTNF‐α, but not the up‐regulation of sTNF‐α in the TNC. Treatment of rats with BzATP induced tactile allodynia/hyperalgesia and up‐regulation of sTNF‐α and p‐p38 in the TNC. Tactile allodynia/hyperalgesia or up‐regulation of sTNF‐α following BzATP treatment was inhibited by SB203580 and etanercept. Conclusions Based on these findings, phosphorylation of p38 MAPK via P2X7R may induce tactile allodynia/hyperalgesia, which is most likely mediated by sTNF‐α released by microglia.